2020
DOI: 10.2147/dmso.s258593
|View full text |Cite
|
Sign up to set email alerts
|

<p>Dapagliflozin Activates Neurons in the Central Nervous System and Regulates Cardiovascular Activity by Inhibiting SGLT-2 in Mice</p>

Abstract: This study investigates the possible effect and central mechanism of novel antidiabetic medication sodium glucose transporter-2 (SGLT-2i) on the cardiovascular activity. Material and Methods: Thirty-four normal male C57BL/6 mice were randomly assigned to 2 groups to receive single Dapagliflozin (1.52mg/kg) dose via intragastric gavage or a comparable dose of saline. Glycemic level (BG), blood pressure (BP) and heart rate (HR) were measured 2 hours after administration of the respective treatments. Immunohistoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 65 publications
2
52
0
5
Order By: Relevance
“… 37 According to one report, SGLT2/SLC5A2 was detected in the hypothalamus, amygdala, periaqueductal gray, and the nucleus of the solitary tract by immunohistochemical analysis. 12 Another report showed that SGLT2/SLC5A2 is present in ependymal cells and choroid plexus epithelial cells. 11 Thus, there is still no consensus regarding which CNS locations express SGLT2/SLC5A2.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 37 According to one report, SGLT2/SLC5A2 was detected in the hypothalamus, amygdala, periaqueductal gray, and the nucleus of the solitary tract by immunohistochemical analysis. 12 Another report showed that SGLT2/SLC5A2 is present in ependymal cells and choroid plexus epithelial cells. 11 Thus, there is still no consensus regarding which CNS locations express SGLT2/SLC5A2.…”
Section: Discussionmentioning
confidence: 99%
“…This assumption is consistent with the sites previously suggested to harbor SGLT2/SLC5A2. 12 Another possibility is that spinal fluid flows from the LV to the lower ventricles, and the SGLT2 inhibitor thereby reaches more SGLT2-expressing ependymal cells expressed around the cerebral ventricle, which may explain why the effect is stronger in the upper ventricles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the context of the parasympathetic nervous system, its activation acts to dampen the SNS and subsequently dull the “fight or flight” response. Recently, Dapagliflozin has been found to regulate cardiovascular activity by increasing the activity of the parasympathetic nervous system in C57Bl/6 mice [ 25 ]. It is well known that the increased activity of the parasympathetic nervous system is associated with increased tyrosine hydroxylase expression [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%